Analyzing the attraction of environmental graphic design at Hang Tuah Centre / Suci Salsabilla Mohd Hidli and Raziq Abdul Samat - Mohd Hidli, Suci Salsabilla; Abdul Samat, Raziq (Kolej Pengajian Seni Kreatif (KPSK) UiTM Cawangan Melaka, 2023)
Malacca is one of the major tourist destinations in Malaysia, with its stunning old colonial buildings, the house of Baba Nyonya, mosques, temples, churches, museums, and decorated trishaws. Malacca is also noted for its unique history. With a highly strategic state position for international trade routes, Malacca was once a well-known international trade center in the East. In 2008, UNESCO declared Malacca a World Heritage Site due to its exceptional example of a multi-cultural trading town and the fact that the town is a living testimony to multi-cultural heritage. The UNESCO World Heritage Site in Malaysia attracts heritage advocates and history enthusiasts. Hang Tuah Centre is one of many interesting places to visit. “Never shall the Malays vanish from this world again,” a powerful statement by Hang Tuah, the legendary Malay warrior, as told by the Malay Annals and Hikayat Hang Tuah. Hang Tuah Centre chronicles the life of Hang Tuah. The centre's complex comprises a cluster of five traditional Malaccan Malay houses which they represent the five famous warriors during the era of Sultan Mansur Shah which are Hang Tuah, Hang Jebat, Hang Kasturi, Hang Lekir and Hang Lekiu. Despite having an identical exterior, each warrior's house displays different exhibits. The centre is located in Kampung Sungai Duyong, where Hang Tuah was born. The main residence of the Hang Tuah Center features slanted wooden panels with floral and geometric bas-relief decorations, tiled staircases, timber walls, and a gable roof. Within it are two galleries, which are Gallery Hang Mahmud and Gallery Dang Merdu. Gallery Hang Mahmud displays Hang Tuah as a great fighter and his legendary clash with his best friend Hang Jebat. Visitors can learn the art of self-defense there. Furthermore, Gallery Dang Merdu presents cultural and historical artefacts related to Hang Tuah.